Students’ Perceptions towards Famous Quotes in Studying Motivation - Waluyo, Yessi Aprilia; Transinata , Tatas; Pratamanti , Enggar Dhian (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2025)
Language can influence the way of thinking, attitude and action of people and give people’s motivation. Famous quote can be the way to increase the motivation from outside into inside because it has important and worthed message and meaning which can influent studying motivation and success motivation. The purpose of this study is to analyse the influence of world figures’ famous quotes based on the perceptions of students at AMIK JTC Semarang. The method used in this study is qualitative method. The results of this study are taken from the analysis of students’ perceptions by using in depth interview. After collecting and managing the qualitative data of interview, coding them, seeking, reviewing and defining the themes and representing, accounting and narrating and reporting the data are the steps of analysing the perceptions of students toward 44 famous quotes in the form of posters at AMIK JTC Semarang. According to the results of data analysis, there are six roles of famous quotes toward the studying motivation of students in AMIK JTC Semarang. In summary, students of AMIK JTC Semarang agree and believe that famous quotes can improve their motivation in studying and achieving the better future